2019
DOI: 10.1177/0954406219848464
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of chip formation in ultrasonic vibration drilling and experimental research

Abstract: When difficult-to-machine materials are drilled, chips are produced, and these chips are difficult to control during the drilling process. Due to the limitations of conventional drilling, materials are drilled by ultrasonic-vibration-assisted technology. In this paper, the kinematics of ultrasonic-vibration-assisted drilling are first analyzed and the relevant equations are established. The characteristic thicknesses of chips are then studied, and the drilling paths for different phases and thicknesses of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Hence, at C1 level, the highest R a is observed that is at 500 RPM. Chen et al [32] also reported that ultrasonic vibration drilling produced a thin and smooth chips while machining of stainless steel.…”
Section: Effects Of Process Parametersmentioning
confidence: 98%
“…Hence, at C1 level, the highest R a is observed that is at 500 RPM. Chen et al [32] also reported that ultrasonic vibration drilling produced a thin and smooth chips while machining of stainless steel.…”
Section: Effects Of Process Parametersmentioning
confidence: 98%
“…The authors presented an analysis of the effects of ultrasonic assisted turning (UAT) on the surface roughness of a wide range of metals and alloys, from copper, aluminum and stainless steels to Ni and Ti based alloys. Results showed that Hybrid Turning Technology UATyields significant improvements in surface roughness for all alloys studied, primarily due to the inherent reduction in cutting forces S.Chen et al [8] performed Ultrasonic assisted vibration drilling to improve the surface finish for drilled holes Surface Roughness is the measure of the quality of a surface being smooth or not. The reduced forces and friction contribute to lower heat generation, which is known to negatively affect surface quality.…”
Section: Introductionmentioning
confidence: 99%
“…However, the drill bit is in a semi-closed state during the drilling process, which makes chip removal very difficult and prone to chip clogging. In addition, when the drill rotates fast, the machining gap is small, and the machining depth is large, the cooling medium does not easily enter the machining area, and it is difficult to cool and lubricate the drill, which increases the temperature of the drilling area and causes serious wear of drill, resulting in poor machining accuracy and easy damage to drill [ 11 , 12 , 13 ]. For hospital stainless steel, titanium alloy, and/or high hardness materials below 0.5 high-precision, small-hole machining is limited by drill strength, tool diameter, table drill speed requirements and/or conditions, and no effective drilling machining means to achieve rapid machining of micro-hole.…”
Section: Introductionmentioning
confidence: 99%